Visualisasi Teknik Kolase Dalam Fotografi Ekspresi "Gurat Karat" - Ketut Gura Arta Laras (Ornamen, 2010)
The selection of photography work object wes not elways inthe beautiful shape. The uniqueness of an object could become its ownattraction end inspiration in creating the photogrephy work. The expres~sion of the composition and vlsuelizetion in a work art became the char~acteristlc of the artist himself.Gural Kerat was a concept of pt1otogrephy work ert which ex~plored the shepe, texture and color of the rust of mete!, especleily inthe rust of iron. We could explore the simple items in our surroundngwhich were not longer used and a/reedy broken. The iron which wasrusted hed its own uniqueness and attraction to obseNe. The chengeof the characteristic and the shape was vety contrast. Before beingrusted, the surface of the iron would be smooth, but after being rusted,the surface would be rough and the color would chenge. It wes a resultof rusting process of the iron itself. The phenomenon eventually stimu~lated the researcher to teke the rust theme of the iron es an object inthis photography work art creation.In arranging this photography work, the researcher used es-thetictheory of Monroe Beardsley which listed three basic estheticcharacteristics as follow: unity, intensity end complexity.The visual work in 3D display created the imege of space anddimension in this work. Colese technique was used in creating this workby combining 2D photography work and the object in the original itemin the photography work itself, or using the construction which was suit~able with the stuck object which was adjusted with the weight of thatobject. In e displey, this work was not only enjoyed by the sense of sightbut also the sanse of touch since the texture in this work art could betouch.Keywords : Expressie Pl1otogrephy, Rust, and Collage